Watch your back - Westlake, Donald (New York. Mysterious Press., 2005)
After a year on the lam, the return of bumbling thief Dortmunder is a cause celebre. The author's most recent Dortmunder caper. "The Road to Ruin," and the short story collection, "Thieves' Dozen," received rave reviews in the "New York Times Book Review, New York Daily News," and "Kirkus Reviews" (starred review), among other publications.
Keywords: Dark Humor; Heist Thrillers; Lawyers & Criminals Humor